The Effectiveness of Behavioral Counseling with Modeling Techniques to Improve Student’s Self Autonomy and Self Endurance - Wulandhari, Ni Nyoman Sri Ayu; Dharsana, I Ketut; Suranata, Kadek (Bisma The Journal of Counseling, 2021)
This study aims to determine the effectiveness of the behavioral counseling model with modeling techniques to improve self-autonomy and self-endurance for senior high school students. This experimental study used a pretest-posttest nonequivalent control group design. Through random sampling, 34 students were placed in the experimental group and 32 students were placed in the control group. Data collection used the main data collection method (questionnaire) and complementary data collection methods (observations, interviews, and diaries). The data were analyzed by One-way MANOVA. The results show that there are differences in self-autonomy and self-endurance in the experimental class and control class ( sig = 0.039). The results of Cohen D analysis showed a high level of effectiveness (ES = 0.8). These results prove that behavioral counseling with modeling techniques is effective for improving student’s self-autonomy and self-endurance.